(untitled) (LEARNing Landscapes, 2010)
The author draws on her experience as a poet and a teacher to offer three key elements for teaching students poetry. She believes that the teacher’s own passion about poetry is the first key to letting the imagination rise.The second key is freedom of mind, both for the teacher and the students, which allows students to explore in many directions, without the constraints of pre-set rules, conventions and grades. The "writing invitation"is the third key. In this part, she outlines several innovative ways to invite students to write poetry, giving them guidelines to start from while allowing their creativity to flourish.